População de Dalbulus maidis (Hemiptera: cicadellidae) e severidade do complexo de enfezamento em função de doses de nitrogênio e potássio em milho - Istchuk, Ademar Novais (2025)
The corn crop has faced significant phytosanitary challenges related to pathogens associated with the corn stunting complex, which can result in yield losses of up to 100%. Despite the importance of these pathogens, current disease control is based on the suppression of the corn leafhopper (Dalbulus maidis), which acts as an insect vector. Control strategies include a set of agricultural practices that combine efforts to achieve better results, as no single practice is highly effective on its own. Aiming to contribute to this set of recommendations, this thesis investigated the effects of the interaction between two corn hybrids and topdressing fertilization with nitrogen and potassium on the incidence of D. maidis and the symptoms expression under field conditions. In total, 18 treatments were tested in randomized blocks with six replications over two seasons. The leafhopper population was monitored throughout the vegetative period using yellow sticky traps. Two evaluations of symptoms were conducted: incidence at R1 and severity at R3. Plant integrity was assessed before manual harvesting to determine yield, and after, the ears were also evaluated and classified based on their quality. The visual scores of corn stunting were grouped and presented as frequency of occurrence, compared to the adopted vigor scale. Statistical analysis was performed using mixed models in R software. A total of 65,711 insects were collected in the first season and 33,781 in the second. The D. maidis population was not influenced by nitrogen or potassium, and no difference was observed between hybrids. Leafhopper density differed between seasons; however, the frequency and severity of symptoms were not proportional to the number of insects collected. Fertilization does not prevent plant infection but can limit symptom expression, especially under conditions of milder symptoms. Topdressing with potassium reduces the visual symptoms of corn stunting at R3. Yield was not influenced by the nutrient rates and hybrids evaluated.